Money Matters: Exploring the Mediating Role of Money Attitudes in the Relationship Between Financial Well-Being and Ginhawa - Khent Rolance T. Tamayo; Jennalla Camilla C. Bayarong; Kervin Justin Mangune; Darwin C. Rungduin; Teresita T. Rungduin (Journal of Financial Therapy, 2026)
Drawing on the Self-Determination Theory, this study acknowledges the increasing financial awareness among young Filipino adults. The COVID-19 economic aftermath prompts focus on young Filipino adults’ financial well-being (FWB) linked to quality of life. Hence, this study investigated how money attitudes help explain the relationship between FWB and ginhawa (Filipino quality of life). An online survey was conducted among 401 young Filipino adults in Metro Manila. The study used correlation analysis to assess the association between FWB and ginhawa, and mediation analysis to test the direct and indirect associations of the variables on ginhawa. Financial well-being is significantly positively associated with ginhawa, while the attitudes toward money are statistically significant in explaining the relationship. The total association shows how FWB is related to ginhawa both directly and indirectly through money attitudes. This research underscores a need to cultivate positive money attitudes to foster the relationship between FWB and ginhawa. The findings support financial counseling and the development of psychoeducation programs to improve financial well-being, foster positive money attitudes, and help individuals achieve ginhawa. Future research should explore additional variables to deepen understanding of the multifaceted nature of FWB and its relationship on ginhawa in young Filipino adults.
Keywords: financial well-being; ginhawa; money attitudes; quality of life; self-determination theory